Productive Subjects Learning Based Quality Management ofISO 9001: 2008 at SMK Negeri 1 Purwokerto - Suprihatin, Elly (2012)
The objectives of the research are to describe (1) the characteristics of productive subjects curriculum based quality management system of ISO 9001: 2008 at SMK Negeri 1 Purwokerto; (2) the characteristics of the learning model of subjects based Quality Management of ISO 9001: 2008 at SMK Negeri 1 Purwokerto; (3) the characteristics of learning interaction of the productive subjects based quality management at SMK Negeri 1 Purwokerto. It is descriptive qualitative research and ethnography design which describes the productive subjects learning based quality management of ISO 9001: 2008. The informants are principal, vice principal, teachers, and students at SMK Negeri 1 Purwokerto. Techniques used in data collection are in-depth interview, documentation and observation. Data analysis of this research includes (1) data collection, (2) data reduction, (3) data display, and (4) conclusion. The research results show that(1) the preparation and development of curriculum is set in SOP (Standard Operating Procedure) and applied by the vice principle of curriculum affairs and the quality management team. The curriculum development involves industrial and business worlds that contribute to facilitate and give input on the curriculum to be applied at the school which is tailored by the need of industrial world. The curriculum preparation team makes a job-sheet with portofolio assessment on the workpiece and form of the curriculum achievement target. (2) Learning is performed using a thorough learning model and learning media base technology such as e-learning, LCD, VCD, and others. The productive learning is held in school and outside of the school through practice program. Learning is supported by the availability of library and laboratories such as Language laboratory, Computer, Business machines, Accounting, Administrative Office, Marketing, Multi Media, and Software Engineering laboratory. To support teaching and learning activities base IT, 30% of the classroom has been completed by LCD. Learning is controlled by supervision and learning evaluation. The evaluation materials should be validated by Quality Assurance team. Learning interaction of the productive subjects base quality management occurs directly and indirectly. The interaction during the learning process in the classroom happens when teachers explain materials with technology-based learning media. The indirect interaction occurs in the learning activities using e-learning media. In industrial work practice activities, students interact with the personnel, work environment, and society.